Strategic analysis of Lady Technologies, Inc. - Uhrin, Patrik; Tyll, Ladislav; Badie, Natálie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2021)
This bachelor thesis aims to perform strategic analysis on Lady Technologies, Inc. and its product kegg and form advice to company management based on this analysis. The bachelor thesis consists of the theoretical and practical part. The theoretical part defines the important terms used during the thesis and describes the theory behind fundamental parts of company strategy and strategic analysis tools and methods used to execute the strategic analysis. The practical part includes a description of Lady Technologies, their product, market, funding, and development details. Tools and methodologies for the strategic analysis described in theoretical part, like analysis of the external and internal environment, are used in practical part to evaluate Lady Technologies’ strategy. Advice to the company’s management is formed in conclusion based on the results of the strategic analysis.
Vedoucí práce: Ladislav Tyll
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: business administration/corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses